Antineoplastic effects of sodium dichloroacetate and omeprazole, alone or in combination, on canine oral mucosal melanoma cells - Toledo, Gabriela F.; Nagamine, Marcia K.; Nowosh, Victor; Machado, Felippe T.; Massoco, Cristina O.; Souza-Pinto, Nadja C.; Dagli, Maria L. Z. (Frontiers in Veterinary Science, 2023)
Abstract: Oral mucosal melanoma (OMM) is a common neoplasm in canines, although it is rare in humans. Cancer cells present alterations in energetic metabolism, and the Warburg effect states that most cancer cells undergo aerobic glycolysis. This can be reversed by certain drugs, resulting in decreased cell viability and cell death. We sought to evaluate the effects of sodium dichloroacetate (DCA) and omeprazole (OMP) alone or in combination on canine OMM and human melanoma cells. CMGD5 and SK-MEL-28 cell lines were treated with DCA and OMP alone or in combination, and cell viability was assessed using the crystal violet assay. Cell death (apoptosis and necrosis) was assessed by Annexin V and propidium iodide (PI) staining assays using flow cytometry. In addition, the oxygen consumption rate (OCR) was evaluated using a SeaHorse XF assay. Treatment with DCA or OMP alone resulted in a significant, but not dose-dependent, reduction in cell viability in both cell lines; however, the combination of DCA and OMP resulted in a significant and dose-dependent decrease in viability in both cell lines. DCA and OMP, alone or in combination, did not alter OCR at the concentrations tested in either cell line. Since the combination of DCA and OMP potentialized the inhibition of viability and increased cell death in a synergistic manner in melanoma cells, this approach may represent a new repurposing strategy to treat cancer.